The Effectiveness of Gain and Loss Frames in News Subscription Appeals. Issue 3 (16th March 2021) - Kim, Yujin; Collier, Jessica; Stroud, Natalie Jomini
Abstract: Subscriptions are an increasingly vital part of newsrooms' business models as the industry experiences sharp declines in advertising revenue. To date, research has not examined how digital subscription appeals affect news subscription intentions. The current study investigates the effectiveness of gain- and loss-framed messages on clicking on subscription appeals, connecting literature on prospect theory and investigations into why people use news. In collaboration with three U.S. newsrooms, we conducted 11 experiments with 222, 385 users, varying whether the message included a gain-framed appeal, a loss-framed appeal, or just stated the cost of the subscription. Across the 11 tests, we also varied the call to action (subscription to newsrooms' newsletter or paid access) and the medium used to distribute the subscription appeal (Facebook Sponsored Posts or direct email). In several tests, loss-framed messages yielded fewer clicks on subscription appeals compared to gain and control messages. Frame performance was moderated by the medium used, with greater effects for email than Facebook. We discuss theoretical and practical implications for how prospect theory can inform our understanding of why people pay for news.